PENGARUH MODAL BANK, KUALITAS KREDIT, UKURAN BANK TERHADAP PERTUMBUHAN KREDIT DENGAN TINGKAT LIKUIDITAS SEBAGAI VARIABEL MODERATING - nurtyas Laras; purwanto purwanto; Ardian Putra Putra (JURNAL MANAJEMEN, 2021)
The purpose of this study was to examine the effect of bank capital, credit quality and bank size on credit growth with liquidity level as a moderating variable. The object used in this study is conventional banking listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. The sample used is 39 banks from a population of 41 banks, using purposive sampling method. This research can be obtained from the bank’s finansial statements. The data analysis technique used is multiple linier regression model and moderated regression analysis (MRA). The results of this study indicate that bank capital has No. significant effect on kredit growth, credit quality has a significant negative effect on kredit growth, bank size has a significant positive effect on kredit growth and the level of liquidity is not able to moderate the relationship between bank capital, kredit quality and bank size with credit growth. Keywords : bank capital, credit quality, bank size, credit growth and liquidity level